Internal flow structures in columnar jointed basalt from Hrepphólar, Iceland: II. Magnetic anisotropy and rock magnetic properties - Almqvist, Bjarne; Bosshard, Sonja; Hirt, Ann; Mattsson, Hannes; Hetényi, György (2018)
The anisotropy of magnetic susceptibility (AMS) and rock magnetic properties were measured on specimens from a basalt plate that was cut from a vertical section of a basalt column from Hrepphólar, Iceland. Macroscopic structures are clearly distinguishable in the plate, including banding inferred to represent viscous fingering parallel to the vertical axis of the column. Rock magnetic experiments indicate that the dominant ferromagnetic (sensu lato) mineral is titanomagnetite, Fe 3−x Ti x O4, with a Ti-composition of x = ~0.6. Magnetic properties are related to the position within the plate and reveal a dominant volume fraction of single domain titanomagnetite in the center of the basalt column, with multidomain titanomagnetite away from the center. The AMS determined by low-field measurements shows an inconclusive relationship with the visual structures, which arises from variation of the grain size (i.e., single domain versus multidomain) across the column. In contrast, the AMS measured with a high-field torsion magnetometer avoids the complication of magnetic domain state, as is demonstrated in this contribution, and additionally allows for the separation of ferrimagnetic from paramagnetic sub-fabrics. Both sub-fabrics display a clear relationship with the macroscopic structures and support the hypothesis that vertical flow of melt took place during development of the Hrepphólar columnar basalt. Maximum susceptibility axes of the ferrimagnetic sub-fabric are grouped near the vertical axis of the column. The paramagnetic sub-fabric varies systematically across the column in coincidence with internal structure. The shape of the magnetic susceptibility ellipsoid varies across the basalt column, showing an increasingly prolate fabric toward its center